PWE-064 Management Of Large Colonic Polyps In The Severn Deanery Hospitals: An Audit Of Current Practice. (9th June 2014) - Dixon, SW; Valliani, T; Fayyaz, F; Tate, D; Arthurs, E; Lim, L; Dhanda, A; Lockett, M
Abstract : Introduction: Large (>2 cm) colonic polyps present a challenge to the colonoscopist. The British Colorectal Cancer Screening Programme (BCSP) recently drafted guidelines to standardise their management. We compared our current practice with the proposed guidelines. Methods: This was a retrospective audit in four South-West hospitals with comparison between screening and non-screening patients. Patients were identified using clinical coding. Case notes were reviewed. Polyps were scored using SMSA system to standardise difficulty of endoscopic resection. Data was compared against 9 auditable outcomes. Results: 104 cases were identified (24 BCSP, 80 symptomatic). There was no significant difference in mean size (2.9 cm BCSP, 2.7 cm symptomatic, p = 0.14) or mean SMSA grading (2.8 BCSP, 2.9 symptomatic, p = 0.46). 6 polyps were malignant (1 BCSP; 5 symptomatic); all had position marked by tattoo. 1 malignant polyp was resected endoscopically in the symptomatic group. Mean time to definitive resection was 34 and 30 days (BCSP and symptomatic respectively). Recurrence of adenoma at EMR site was low at 3 months (0/22 BCSP, 1/37 symptomatic) and 12 months (0/22 BCSP, 2/37 symptomatic). However fewer EMR sites were checked if the index endoscopy was performed by a non-BCS colonoscopist (10/13 vs. 8/24). Complication rates were low: 1 haemorrhage requiring admission (symptomatic group); 0 perforations. 17 benign polyps were referred for surgery (3 BCSP, 14 symptomatic; p = 0.49). In both groups the mode SMSA score was 4. Benign polyps were referred directly for surgery; only those polyps with malignant histology were discussed at a formal mutli-disciplinary meeting. There were no deaths or signficant morbidity associated with surgery for bening polyps. Conclusion: Overall management was comparable to draft guidelines. The frequency of large polyps outside BCSP indicates that non-BCS endoscopists will gain experience with these lesions. Approximately 17% of benign polyps were referred for surgery, similar to other series. However, none had been discussed with local EMR experts. Consequently a large polyp referral pathway has been established at two centres within the region. Reference: Gupta S, Miskovic D, Bhandari P, et al . SMSA scoring system: a novel scoring system for determining the level of difficulty of a polypectomy. Gastrointestinal Endoscopy 2011;73(4S):AB418–9 Disclosure of Interest: None Declared.